Appeal of suspension: Canon 1353 - Provost, James H. (Roman replies and CLSA advisory opinions 1995, 1995)
If a penalized priest were to appeal a suspension, what would be the proper dicastery? In light of canon 1353 (the suspensive effect of an appeal) would the priest continue his pastorate with faculties during the course of the appeal?